Family functioning, family social support, and life satisfaction among school adolescents in the Federal Land Development Authority (FELDA) area in Johor, Malaysia - Jaafar, Siti Nor Jannah; Azam, Naqi Dahamat; Rosnon, Mohd Roslan; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
Adolescents' satisfaction with life can be influenced by various factors, including family environment factors. This study aimed to ascertain the relationship between family functioning and social support on adolescents’ life satisfaction in Johor, Malaysia. A total of 575 school adolescents from FELDA areas in Johor participated in this study. The data was collected via self-administered questionnaires, which consisted of the Satisfaction with Life Scale, the Family Assessment Device, and the Multidimensional Scale of Perceived Social Support. Correlation and multiple regression analyses were conducted using IBM SPSS version 25. The results showed a significant positive connection between family functioning and family support on life satisfaction. Further analyses showed that family social support significantly predicted life satisfaction. In conclusion, this study highlights the critical role of family functioning and social support in determining adolescents' life satisfaction, with family social support emerging as the sole significant predictor. These findings emphasize the importance of a supportive family environment in enhancing the well-being of adolescents in FELDA areas in Johor.